Shelf life extension of individually film-wrapped mangoes - Yamashita, F. [UNESP]; Benassi, M. T. [UNESP]; Kieckbusch, T. G. (My University, 1997)
Mangoes cv. Keitt were individually sealed in a heat-shrinkable polyolefin film (D-955) and a low-density polyethylene film (LDPE), stored for 0-5 weeks at 12°C and 17°C, and then ripened unwrapped at 22°C. Weight loss of packaged mangoes was significantly lower than that of the non-wrapped control. A sensory panel ranked the mangoes for overall eating quality and appearance. D-955 and LDPE film-sealed mangoes and control had shelf lives of 33, 15 and 7 days at 12°C and 17,10 and 7 days at 17°C, respectively.
Keywords: Mango; Modified atmosphere; Sensory evaluation; Shrink-wrap